PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 006 TELUK MAKMUR - Sunarti '; Hendri Marhadi Hendri Marhadi; Gustimal witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This research is motivated by low yields social studies Student Class V Prosperous Bay Elementary School 006, Average - The average grade 55 with a minimum completeness criteria values ​​(KKM) IPS is 70 students totaling 20 people only 10 students who reached the KKM. And that does not reach the KKM 10 people. This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPS Elementary School fifth grade students by applying 006 Prosperous Bay STAD cooperative learning model. Formulation of the problem: Is the implementation of STAD cooperative learning model to improve learning outcomes IPS Elementary School fifth grade students 006 Prosperous Bay. This study was conducted on April 7, 2014 to April 17, 2014 with two cycles. The subjects were students of class V Elementary School 006 Gulf Makmur which about 20 people were used as a source of data. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. Article this study presents the results obtained from the value of the daily tests before treatment with an average of 55, increased in the first cycle with the average being 77.5. In the second cycle increases with - average 85 Activity of teachers in the learning process in the first cycle of the meeting 58.33%, the second meeting increased to 62.5%. Cycle II meeting the 70.8% (Enough), the second meeting be 79.16% (Good). The results of the data analysis of student activity at the first meeting of the cycle with an average of 54.16% second meeting be 66.6%, the second meeting of the Cycle to increase to 75% (enough) the second meeting increased to 83.3% (good). Based on the research results in class V Prosperous Bay Elementary School 006 that the application of STAD cooperative learning model to improve learning outcomes IPS Elementary School fifth grade students 006 Prosperous Bay. Keywords: Cooperative Learning Model of type Student Achievement Divisions (STAD), the results of social studies